1, 4‐Dioxane: Emerging technologies for an emerging contaminant. Issue 4 (11th September 2019) - Broughton, Anita; Sepulveda, Andrea; Foster, Keith; Kruk, Taras; Nickelsen, Michael G.; Gillan, Maleya; Mohr, Thomas K.G.
Abstract: The synthetic chemical, 1, 4‐dioxane, is classified by the U.S. Environmental Protection Agency (EPA) as a probable human carcinogen. Between 2013 and 2015, the EPA detected 1, 4‐dioxane in public drinking water supplies in 45 states at concentrations up to 33 µg/L and in groundwater from releases at hazardous waste sites across the United States. Although a Federal maximum contaminant level drinking water standard has not yet been proposed, state‐specific standards and criteria are as low as 0.3 µg/L. 1, 4‐Dioxane is a recalcitrant chemical in that applications of conventional treatment technologies have had limited success in reducing concentrations in water to meet current and proposed health‐protective levels. Although mainly used as a stabilizer for the solvent 1, 1, 1‐trichloroethane, it has been used in other industrial processes and has been detected in a variety of consumer products, such as foods, pharmaceuticals, cosmetics, and detergents. The high aqueous solubility of 1, 4‐dioxane coupled with limited solubility of chlorinated solvents typically found in conjunction with 1, 4‐dioxane contamination is the primary reason for its treatment challenges. In the last several years, an alternative, cost‐effective technology has been developed that has demonstrated treatment to levels significantly lower than the Federal and state‐specific goals. This article provides a Federal and state‐by‐state summary of 1, 4‐dioxane‐specific drinking water and groundwater concentration criteria and qualitative comparison of the effectiveness of conventional treatment technologies compared to the effectiveness of an alternative treatment technology. A case study is also provided to present details regarding the application of an alternative treatment technology at an active groundwater remediation site in California.